Research Progress on the Mechanism of Acupuncture Treatment for Nonalcoholic Fatty Liver Disease - Bai Li; Li Fang (Gastroenterology Research and Practice)
Nonalcoholic fatty liver disease (NAFLD) represents the most common chronic liver disease worldwide, ranging from simple steatosis and nonalcoholic steatohepatitis to fibrosis, cirrhosis, and hepatocellular carcinoma. Acupuncture is a long-established treatment in traditional Chinese medicine. In recent years, increasing evidence has pointed to the effectiveness of acupuncture in the treatment of NAFLD, and a certain degree of progress has been made in the study of related mechanisms. However, previous systematic reviews have not discussed the characteristics and the related mechanisms of acupuncture in the treatment of NAFLD. Therefore, this review synthesizes the progress in research on acupuncture in the context of NAFLD treatment by the inhibition of inflammatory responses, regulation of lipid metabolism disorder, treatment of insulin resistance, antagonization of oxidative stress injury, and interference with endoplasmic reticulum stress. Overall, we sought to highlight the latest research results, potential applications, and ongoing challenges of this therapy.